Sistem Informasi Warehouse Management System (WMS) Pada PT. Citra Banjar Abadi - Nina Rahayu; Yazid Ma’ruf; Aditya Sunarsa (UNIVERSITAS RAHARJA, 2022)
PT. Citra Banjar Abadi is a company engaged in the distribution of Raw Material goods for the needs of making extra high voltage overhead line towers or what we know as SUTET. The problems that occur at PT. Citra Banjar Abadi at this time is for the warehouse information system, especially for data processing, it still uses Ms. Excel, so it has risks in terms of security and lack of guaranteed accuracy of data items, etc. The system analysis method used is the SWOT method which is suitable to be applied in this research, then the system design method is described by UML diagrams, programming language with PHP, database using MySQL and programming software with Sublime and XAMPP. The application of the Warehouse Management System (WMS) information system created from this research is expected to be the right solution to solve existing problems, because the purpose of implementing this WMS is to make ongoing business processes more effective, time and resource efficient.